HERC5 is a prognostic biomarker for post-liver transplant recurrent human hepatocellular carcinoma. Issue 1 (December 2015) - Xue, Feng; Higgs, Brandon; Huang, Jiaqi; Morehouse, Chris; Zhu, Wei; Yao, Xin; Brohawn, Philip; Xiao, Zhan; Sebastian, Yinong; Liu, Zheng; Xia, Yun; Shen, Dong; et al.
Abstract Background and aims Orthotopic liver transplantation (OLT) can be an effective treatment option for certain patients with early stage hepatocellular carcinoma (HCC) meeting Milan, UCSF, or Hangzhou criteria. However, HCC recurrence rates post-OLT range from 20 to 40 %, with limited follow-up options. Elucidating genetic drivers common to primary and post-OLT recurrent tumors may further our understanding and help identify predictive biomarkers of recurrence—both to ultimately help manage clinical decisions for patients undergoing OLT. Methods Whole exome and RNA sequencing in matched primary and recurrent tumors, normal adjacent tissues, and blood from four Chinese HCC patients was conducted. SiRNA knockdown and both qRT-PCR and Western assays were performed on PLCPRF5, SNU449 and HEPG2 cell lines; immunohistochemistry and RNA Sequencing were conducted on the primary tumors of Chinese HCC patients who experienced tumor recurrence post-OLT (n = 9) or did not experience tumor recurrence (n = 12). Results In three independent HCC studies of patients undergoing transplantation (n = 21) or surgical resection (n = 242, n = 44) of primary tumors (total n = 307), HERC5 mRNA under-expression correlated with shorter: time to tumor recurrence (p = 0.007 and 0.02) and overall survival (p = 0.0063 and 0.023), even after adjustment for relevant clinical variables.HERC5 loss drives CCL20 mRNA and protein over-expression and associates with regulatory T cell infiltration as measured by FOXP3 expression. Further, matched primary and recurrent tumors from the 4 HCC patients indicated clonal selection advantage of Wnt signaling activation and CDKN2A inactivation. Conclusions HERC5 plays a crucial role in HCC immune evasion and has clinical relevance as a reproducible prognostic marker for risk of tumor recurrence and survival in patients.